Unstressed Syllables for Pre-Intermediate Learners - Miklas, Matthew (Thammasat Review, 2015)
Being a stress-timed language, the teaching of English presents a problem in how to approach the very pervasive issue of proper word and sentence stress. Teachers often draw attention to and practice this issue by enabling students to notice and emphasize stressed syllables. A more novel approach is to have learners notice and perhaps secondarily attempt production of reduced syllables. This article contains an analysis of the issue of the occurrence of the schwa in reduced syllables with an eye to how to promote students’ ability to notice the unstressed syllables and, by extension, their relation to stressed syllables. Keyword: Stress-Timed, Pervasive, Emphasize Stressed, Syllables